Capsaicin Prevents Contrast-Associated Acute Kidney Injury through Activation of Nrf2 in Mice. (16th May 2022) - Ran, Fei; Yang, Yi; Yang, Lun; Chen, Shichao; He, Ping; Liu, Qiting; Zou, Qingliang; Wang, Dan; Hou, Jixin; Wang, Peijian
Abstract : Capsaicin, a transient receptor potential vanilloid 1 channel agonist, possesses antioxidative properties through activating nuclear factor-erythroid 2-related factor 2 (Nrf2). As oxidative stress is a major contributor to the development of contrast-associated acute kidney injury (CA-AKI), we investigated the protective effect of capsaicin against CA-AKI via Nrf2. C57BL/6J mice were treated with dehydration and iodixanol to establish the model of CA-AKI. For pretreatment, capsaicin (0.3 mg/kg) was given via intraperitoneal injection one hour before iodixanol injection. Nrf2-specific siRNA was given through the tail vein to knock down Nrf2. The CA-AKI mouse model had remarkable mitochondrial fragmentation and dysfunction and apoptosis of tubular cells, overproduction of superoxide in renal tubules, increased renal malondialdehyde, tubular epithelial cell injury, and renal dysfunction. Importantly, pretreatment with capsaicin significantly ameliorated tubular cell injury and renal dysfunction with decreased superoxide, renal malondialdehyde, and apoptotic tubular cells and improved mitochondrial morphology and function in the CA-AKI mouse model. The expression of Nrf2 was increased in the kidney from the CA-AKI mouse model and was further enhanced by capsaicin. Administration of siRNA through the tail vein successfully decreased Nrf2 expression in the kidney, and knockdown of Nrf2 by siRNA abolished the beneficial effects of capsaicin on CA-AKI. The present study demonstrated a protective effect of capsaicin pretreatment against CA-AKI via Nrf2.